Laminate and adhesive tape
Patent Information
- Application Number
- JP2020012906
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-01-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-01-29
AI Technical Summary
【0007】 本発明によれば、優れた電磁波シールド性及び柔軟性を有し、かつ少なくとも一方の面及び積層方向に沿って絶縁性を有する積層体及び粘着テープを提供することができる。
Smart Images

Figure 0007629688000003 
Figure 0007629688000001 
Figure 0007629688000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate and a pressure-sensitive adhesive tape including the laminate. [Background technology]
[0002] The circuit boards of electronic devices such as mobile phones, cameras, game devices, electronic organizers, and personal computers are densely packed with active components such as integrated circuits (ICs), bipolar transistors, and field effect transistors (FETs), as well as passive components such as resistors, capacitors, and coils. Due to the demand for smaller and thinner electronic devices, the spacing between components in electronic devices has become very narrow, making it easier for interference between components to occur due to electromagnetic noise. Furthermore, electronic devices are increasingly being made of plastic due to the demand for lighter weight and lower cost, resulting in a situation where internal noise leaks from inside the electronic device, or external noise from outside the electronic device causes interference to components installed in the electronic device.
[0003] In order to suppress the effects of electromagnetic noise, measures have been taken to install conductive buffer materials between components of electronic devices and inside the housings as components that reflect or absorb and block electromagnetic noise (see, for example, Patent Document 1). Also, it has been proposed to install electromagnetic shielding materials in which a metal layer is formed by a sputtering method in electronic devices as components that block electromagnetic noise (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-92193 A [Patent Document 2] JP 2015-88658 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, since the conductive buffer material described in Patent Document 1 is conductive, there is a problem that an unexpected current flows when the conductive layer of the conductive buffer material touches the circuit of an electronic device, causing the electronic device to malfunction. Also, the electromagnetic noise countermeasure component described in Patent Document 2 has a problem that it has low flexibility and poor conformability to the component on which it is installed, since it has a metal layer, etc. The present invention has been made in consideration of the above problems, and has an objective of providing a laminate and adhesive tape that have excellent electromagnetic shielding properties and flexibility, and that have insulating properties on at least one surface and along the lamination direction. [Means for solving the problem]
[0006] As a result of extensive investigations, the present inventors have found that a laminate having a prescribed laminate structure, 25% compressive strength and electromagnetic wave shielding property can solve the above problems, and have completed the present invention as described below. That is, the present invention provides the following [1] to
[13] . [1] A laminate comprising a conductive resin layer and an insulating resin layer laminated on at least one surface of the conductive resin layer, the laminate having a 25% compressive strength of 30 kPa or more and 800 kPa or less and an electromagnetic wave shielding property of 10 dB or more at a frequency of 100 MHz measured by the coaxial method. [2] The surface resistance of the conductive resin layer is 1.0 × 10 3 The laminate according to [1], having a resistivity of Ω / sq or less. [3] The surface resistance of the insulating resin layer is 1.0×10 7 The laminate according to [1] or [2], having a resistance of Ω / sq or more. [4] The laminate according to any one of [1] to [3], wherein the conductive resin layer contains a polyolefin resin and a conductive filler. [5] The laminate according to [4], wherein the conductive filler is a carbon-based filler. [6] The laminate according to any one of [1] to [5], wherein the insulating resin layer contains a polyolefin resin. [7] The laminate according to any one of [4] to [6], wherein the polyolefin-based resin comprises at least one selected from the group consisting of a polyethylene-based resin, a polypropylene-based resin, and an olefin-based elastomer. [8] Density: 0.06 g / cm 3 More than 0.7g / cm 3 The laminate according to any one of [1] to [7] below. [9] The laminate according to any one of [1] to [8], which has a thickness of 0.01 mm or more and 2.0 mm or less.
[10] The laminate according to any one of [1] to [9], which has no electrical conductivity in the stacking direction.
[11] The laminate according to any one of [1] to
[10] , wherein at least one of the conductive resin layer and the insulating resin layer is a layer made of a foam.
[12] The laminate according to
[11] , wherein the layer made of the foam is crosslinked.
[13] An adhesive tape comprising the laminate according to any one of [1] to
[12] and an adhesive layer provided on at least one surface of the laminate. Effect of the Invention
[0007] According to the present invention, it is possible to provide a laminate and a pressure-sensitive adhesive tape having excellent electromagnetic wave shielding properties and flexibility, and also having insulation properties on at least one surface and along the lamination direction. [Brief description of the drawings]
[0008] [Figure 1] 1 is a cross-sectional view of a laminate according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in further detail below with reference to embodiments. [Laminate] The laminate of the present invention comprises a conductive resin layer and an insulating resin layer laminated on at least one surface of the conductive resin layer, and has a 25% compressive strength of 30 kPa or more and 800 kPa or less, and an electromagnetic wave shielding property of 10 dB or more at a frequency of 100 MHz measured by the coaxial method.
[0010] 1(a), the laminate according to the embodiment of the present invention has a configuration in which insulating resin layers 20 are provided on both sides of a conductive resin layer 10. In a laminate in which insulating resin layers 20 are provided on both sides of a conductive resin layer 10, the insulating resin layers 20 are provided on the outermost layers on both sides in the stacking direction D, thereby making it possible to prevent electrical conduction between the outermost layers in the stacking direction D. 1(b), the laminate according to the embodiment of the present invention has a configuration in which an insulating resin layer 20 is provided on one side of a conductive resin layer 10. A laminate having an insulating resin layer 20 on one side of a conductive resin layer 10 has conductivity in the surface direction of the conductive resin layer 10 because the conductive resin layer 10 is provided on one of the outermost layers in the stacking direction D. However, in this configuration, because the insulating resin layer 20 is provided on the other outermost layer in the stacking direction D, it is possible to prevent electrical conduction between the outermost layers in the stacking direction D.
[0011] (Conductive resin layer) The conductive resin layer has electrical conductivity and a function of blocking electromagnetic noise. The conductive resin layer preferably contains a polyolefin resin and a conductive filler. The conductive resin layer may be a foam or a bulk (non-foam), or may be a combination of a foam and a bulk. A foam conductive resin layer can improve flexibility and impact absorption. A bulk conductive resin layer has good mechanical strength. The conductive resin layer as a foam can be formed by foaming a conductive resin composition containing a foaming agent in addition to a polyolefin resin and a conductive filler. From the viewpoint of obtaining mechanical strength, the conductive resin layer as a foam is preferably one obtained by crosslinking and foaming the conductive resin composition.
[0012] <Polyolefin resin> The polyolefin resin preferably contains at least one selected from the group consisting of polyethylene resins, polypropylene resins, and olefin elastomers, and among these, polyethylene resins are preferred.
[0013] 《Polyethylene resin》 Examples of polyethylene resins include ethylene homopolymers, ethylene-α-olefin copolymers, and ethylene-vinyl acetate copolymers. Ethylene-α-olefin copolymers are polyethylene resins obtained by copolymerizing ethylene with an α-olefin, with ethylene being the main component (usually 70% by mass or more, preferably 90% by mass or more of the total monomers). Specific examples of the α-olefins constituting the polyethylene resins include propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, and 1-octene. Furthermore, the ethylene-vinyl acetate copolymer usually includes a copolymer in which ethylene accounts for 50% by mass or more of the total monomers. The polyethylene resin may be any of linear low-density polyethylene, low-density polyethylene, medium-density polyethylene, and high-density polyethylene, but linear low-density polyethylene and low-density polyethylene are preferred. The density of linear low-density polyethylene and low-density polyethylene is 0.870 to 0.930 g / cm 3 is preferable, and 0.875 to 0.925 g / cm 3 More preferably, 0.880 to 0.921 g / cm 3 As the polyethylene resin, a plurality of polyethylene resins may be used, and a polyethylene resin having a density outside the above-mentioned range may be added.
[0014] <Polypropylene resin> Examples of polypropylene-based resins include propylene homopolymers, propylene-α-olefin copolymers obtained by copolymerizing propylene with an α-olefin, with propylene as the main component (usually 70% by mass or more, preferably 90% by mass or more of the total monomers), etc. These may be used alone or in combination of two or more kinds. Specific examples of the α-olefin constituting the propylene-α-olefin copolymer include ethylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, and 1-octene.
[0015] Olefin elastomer Examples of the olefin-based elastomer include ethylene-propylene random copolymer rubber and olefin-based thermoplastic elastomer (TPO).
[0016] <Ethylene-propylene random copolymer rubber> The ethylene-propylene random copolymer rubber may have other monomer units in addition to the ethylene unit and the propylene unit. Examples of monomers forming the other monomer units include conjugated dienes having 4 to 8 carbon atoms, such as 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 1,3-pentadiene, and 2,3-dimethyl-1,3-butadiene; non-conjugated dienes having 5 to 15 carbon atoms, such as dicyclopentadiene, 5-ethylidene-2-norbornene, 1,4-hexadiene, 1,5-dicyclooctadiene, 7-methyl-1,6-octadiene, and 5-vinyl-2-norbornene; vinyl ester compounds such as vinyl acetate; unsaturated carboxylic acid esters such as methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, and ethyl methacrylate; and unsaturated carboxylic acids such as acrylic acid and methacrylic acid. These monomers may be used alone or in combination of two or more. Among these, non-conjugated dienes having 5 to 15 carbon atoms are preferred, and from the viewpoint of availability, 5-ethylidene-2-norbornene, 1,4-hexadiene, and dicyclopentadiene (DCPD) are more preferred, with 5-ethylidene-2-norbornene being even more preferred. These ethylene-propylene random copolymer rubbers can be used alone or in combination of two or more kinds.
[0017] <Olefin-based thermoplastic elastomer (TPO)> Olefin thermoplastic elastomers (TPO) generally consist of polyolefin resins such as polyethylene resins and polypropylene resins as hard segments, and polyolefin rubbers such as EPR and EPDM as soft segments. TPO can be of any of the blend type, dynamic crosslinking type, and polymerization type.
[0018] Other resin components The resin components constituting the laminate may contain only polyolefin resins, but may contain resin components other than polyolefin resins as long as the object of the present invention is not hindered. Examples of resin components other than polyolefin resins include various elastomers. The elastomer is not particularly limited, but may also be, for example, acrylonitrile butadiene rubber, natural rubber, polybutadiene rubber, polyisoprene rubber, styrene-butadiene block copolymer, hydrogenated styrene-butadiene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer, hydrogenated styrene-isoprene block copolymer, hydrogenated styrene-isoprene-styrene block copolymer, etc. Furthermore, the resin components constituting the laminate do not necessarily need to contain a polyolefin resin, and may be composed of other resin components.
[0019] <Conductive filler> The conductive filler is a filler that has high conductivity and improves the conductivity of the conductive resin layer. Examples of the conductive filler contained in the conductive resin layer include carbon-based fillers and metal-based fillers, and among them, carbon-based fillers are preferable. The conductive filler may be used alone or in combination of two or more kinds. The content of the conductive filler is preferably 20% by mass or more and 70% by mass or less, more preferably 30% by mass or more and 60% by mass or less, and even more preferably 40% by mass or more and 50% by mass or less, based on the total amount of the conductive resin layer. By having the content of the conductive filler within the above range, the conductivity of the conductive resin layer can be improved, and the electromagnetic wave shielding property of the laminate can be improved.
[0020] Carbon-based filler Examples of the carbon-based filler include graphite, carbon black, and carbon nanotubes.
[0021] <graphite> Examples of the shape of graphite include scaly, acicular, fibrous, spherical, flake, agglomerated, and porous. Of these, scaly is preferable. One type of graphite may be used alone, or two or more types may be used in combination. The scaly graphite is not particularly limited as long as it is a carbon-based filler having a scaly shape. Scaly graphite has a large particle aspect ratio, exhibits high conductivity in the major axis direction, and can improve the conductivity of the conductive resin layer. Here, the aspect ratio means thickness / major axis. In this specification, the aspect ratio is an average aspect ratio, and specifically, it is obtained by observing 50 arbitrarily selected particles with an electron microscope or optical microscope and calculating the average value of thickness / major axis of each particle. The aspect ratio of the scaly graphite is preferably 0.001 to 0.200, more preferably 0.005 to 0.150, and even more preferably 0.010 to 0.100.
[0022] The average particle size (major axis) of the scaly graphite is preferably 10 μm or more and 500 μm or less, more preferably 15 μm or more and 400 μm or less, and even more preferably 20 μm or more and 300 μm or less. When the average particle size (major axis) of the scaly graphite is equal to or less than the upper limit, the dispersibility of the scaly graphite in the conductive resin composition can be improved. When the average particle size (major axis) of the scaly graphite is equal to or more than the lower limit, the probability of contact between the scaly graphite particles increases, and the conductivity can be improved. Here, the average particle size is, for example, a value obtained by thoroughly dispersing the scaly graphite in a THF solution, measuring the particle size using a laser diffraction particle size distribution analyzer (manufactured by Shimadzu Corporation, product name "SALD-2200"), and averaging the measured particle size.
[0023] The content of the scaly graphite is preferably 20% by mass or more and 70% by mass or less, more preferably 25% by mass or more and 60% by mass or less, and even more preferably 30% by mass or more and 50% by mass or less, based on the total amount of the conductive resin layer. By having the content of the scaly graphite within the above range, the contact probability between the scaly graphite particles can be ensured, and the conductivity can be improved.
[0024] Carbon Black The shape of the carbon black is not particularly limited, and examples of the carbon black include hollow carbon-based fillers such as Ketjenblack, which has a hollow shape with a hollow interior. Carbon black can form a conductive path by chaining together, improving the conductivity of the conductive resin layer. In order for carbon black to be well chained together, the dibutyl phthalate (DBP) oil absorption of carbon black is preferably 100 mL / 100 g or more, more preferably 200 mL / 100 g or more, and even more preferably 300 mL / 100 g or more. When the DBP oil absorption of carbon black is equal to or more than the lower limit, the carbon black can be well bonded together and a wide conductive path can be formed. Here, the DBP oil absorption of carbon black can be measured in accordance with JIS K 6217-4:2008 using, for example, an absorption meter (manufactured by Asahi Research Institute, product name "S500").
[0025] The primary particle diameter of carbon black is preferably 5 nm or more and 100 nm or less, more preferably 7 nm or more and 80 nm or less, and even more preferably 10 nm or more and 60 nm or less. When the primary particle diameter of carbon black is within the above range, dispersibility is good, and bonding between carbon black particles is good, so that a wide conductive path can be formed. Here, the primary particle diameter of carbon black can be determined by measuring the diameters of 100 particles using a transmission electron microscope and calculating the average value.
[0026] The carbon black content is preferably 0.01% by mass to 20% by mass, more preferably 0.1% by mass to 15% by mass, and even more preferably 0.5% by mass to 10% by mass, based on the total amount of the conductive resin layer. By keeping the carbon black content within the above range, the probability of contact between carbon black particles can be ensured, and electrical conductivity can be improved.
[0027] Carbon nanotubes Carbon nanotubes are tubular carbon polyhedrons with a cylindrical closed graphite sheet structure, the main structure of which is a six-membered carbon ring structure, and are hollow fibers. The type of carbon nanotube used in the present invention is not particularly limited, and may be a single-walled carbon nanotube or a multi-walled carbon nanotube. The single-walled carbon nanotube is a carbon nanotube having a structure in which one graphite sheet is closed in a cylindrical shape, and the multi-walled carbon nanotube is a carbon nanotube having a multi-layered structure in which multiple graphite sheets are closed in a concentric cylindrical shape.
[0028] The outer diameter of the carbon nanotube used in the present invention is not particularly limited, but from the viewpoint of reducing the surface resistance value of the conductive resin layer, it is preferably 0.1 nm to 300 nm, more preferably 0.3 nm to 100 nm, and even more preferably 0.5 nm to 20 nm. The outer diameter of the carbon nanotube is measured by a transmission electron microscope. From the same viewpoint, the length of the carbon nanotube is preferably 0.01 μm or more and 1000 μm or less, more preferably 0.1 μm or more and 800 μm or less, and further preferably 1 μm or more and 600 μm or less. The length of the carbon nanotube is measured by an atomic force microscope.
[0029] The carbon nanotube content is preferably 20% by mass or more and 70% by mass or less, more preferably 25% by mass or more and 60% by mass or less, and even more preferably 30% by mass or more and 50% by mass or less, based on the total amount of the conductive resin layer. By keeping the carbon nanotube content within the above range, the probability of contact between the carbon nanotubes can be ensured, and the conductivity can be improved.
[0030] Carbon nanotubes can generally be produced by catalytic flow chemical vapor deposition (CCVD), chemical vapor deposition (CVD), laser ablation, arc discharge, or the like. An example of a commercially available carbon nanotube is "TUBALL" manufactured by OCSiAl.
[0031] Metal filler The metallic filler is not particularly limited, and examples thereof include metals such as gold, silver, platinum, aluminum, copper, iron, nickel, palladium, chromium, and stainless steel, as well as metal powders, metal flakes, and metal fibers made of alloys thereof. The content of the metal filler is preferably 20% by mass or more and 60% by mass or less, more preferably 25% by mass or more and 55% by mass or less, and even more preferably 30% by mass or more and 50% by mass or less, based on the total amount of the conductive resin layer. By having the content of the metal filler within the above range, the contact probability between the metal fillers can be ensured, and the conductivity can be improved.
[0032] The average particle size of the metal filler is preferably 0.1 μm or more and 30 μm or less, more preferably 0.5 μm or more and 25 μm or less, and even more preferably 1.0 μm or more and 20 μm or less. When the average particle size of the metal filler is within the above range, the dispersibility is improved and the electrical conductivity can be improved. Here, the average particle size of the metal filler is defined as d50 measured by a laser diffraction / scattering method.
[0033] <Foaming agent> As the foaming agent, a thermally decomposable foaming agent can be used. For example, a chemical foaming agent such as an organic foaming agent or an inorganic foaming agent having a decomposition temperature of about 160 to 270° C. can be used. Examples of organic blowing agents include azo compounds such as azodicarbonamide, metal azodicarboxylates (e.g., barium azodicarboxylate), and azobisisobutyronitrile; nitroso compounds such as N,N'-dinitrosopentamethylenetetramine; hydrazine derivatives such as hydrazodicarbonamide, 4,4'-oxybis(benzenesulfonylhydrazide), and toluenesulfonylhydrazide; and semicarbazide compounds such as toluenesulfonylsemicarbazide. Examples of inorganic foaming agents include ammonium carbonate, sodium carbonate, ammonium hydrogen carbonate, sodium hydrogen carbonate, ammonium nitrite, sodium borohydride, and anhydrous monosodium citrate. As the foaming agent, from the viewpoint of obtaining fine bubbles, and from the viewpoints of economy and safety, azo compounds and nitroso compounds are preferred, azodicarbonamide, azobisisobutyronitrile and N,N'-dinitrosopentamethylenetetramine are more preferred, and azodicarbonamide is particularly preferred. These foaming agents can be used alone or in combination of two or more. The amount of the foaming agent added is preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, and even more preferably 3 to 10 parts by mass, per 100 parts by mass of the resin component. When the amount of the foaming agent added is within the above range, the bubbles of the foam can be appropriately foamed without bursting.
[0034] <Other additives> The foamable composition of the present invention may contain additives such as a decomposition temperature regulator, an antioxidant, a foaming assistant, a crosslinking assistant, a flame retardant, a metal damage inhibitor, an antistatic agent, a stabilizer, a filler, and a pigment, as necessary.
[0035] Examples of the decomposition temperature regulator include magnesium oxide, magnesium hydroxide, zinc oxide, zinc stearate, urea, etc. The decomposition temperature regulator may be used alone or in combination of two or more kinds. The content of the decomposition temperature regulator is preferably from 0.1 to 10 parts by mass, more preferably from 0.2 to 5 parts by mass, and further preferably from 0.3 to 3 parts by mass, based on 100 parts by mass of the resin component.
[0036] Examples of the antioxidant include phenol-based antioxidants, sulfur-based antioxidants, phosphorus-based antioxidants, and amine-based antioxidants. Among these, the phenol-based antioxidants and sulfur-based antioxidants are preferred, and it is more preferred to use a combination of a phenol-based antioxidant and a sulfur-based antioxidant. Examples of the phenol-based antioxidant include 2,6-di-tert-butyl-p-cresol, n-octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenylacrylate, tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane, etc. These phenol-based antioxidants may be used alone or in combination of two or more kinds. Examples of sulfur-based antioxidants include dilauryl thiodipropionate, dilauryl thiodipropionate, dimyristyl thiodipropionate, distearyl thiodipropionate, pentaerythrityl tetrakis(3-lauryl thiopropionate), etc. These sulfur-based antioxidants may be used alone or in combination of two or more kinds. The content of the antioxidant is preferably from 0.1 to 10 parts by mass, more preferably from 0.2 to 5 parts by mass, and further preferably from 0.3 to 3 parts by mass, relative to 100 parts by mass of the resin component.
[0037] (Insulating resin layer) The insulating resin layer has a property of being difficult to conduct electricity and has a function of blocking the flow of electricity in the stacking direction of the laminate. The conductive resin layer preferably contains a polyolefin resin. The insulating resin layer may be a foam or a bulk body, or may be a combination of a foam and a bulk body, but is preferably a foam. The insulating resin layer that is a foam can improve flexibility and impact absorption. The insulating resin layer as a foam can be formed by foaming an insulating resin composition containing a foaming agent in addition to a polyolefin resin. From the viewpoint of obtaining mechanical strength, the insulating resin layer as a foam is preferably one obtained by crosslinking and foaming the insulating resin composition. In addition, the polyolefin resin, other resin components, foaming agent, and other additives contained in the insulating resin layer can be the same materials as those described for the conductive resin layer, and the details are the same as those described above, so they will not be described again.
[0038] (Layer structure of laminate) As the layer structure of the laminate, the insulating resin layer is preferably a foam structure. When the insulating resin layer is a foam, the flexibility and impact absorption of the laminate can be improved. As the layer structure of the laminate, more preferably, the insulating resin layer is a foam and the conductive resin layer is a bulk structure. When the insulating resin layer is a foam, the flexibility and impact absorption of the laminate can be improved, and when the conductive resin layer is a bulk, the mechanical strength of the laminate becomes good, and the laminate has a function as a core material, so that the handling property can be improved. As the layer structure of the laminate, more preferably, the insulating resin layer is a foam, the insulating resin layer is provided on the outermost layer on both sides of the laminate, and the conductive resin layer is a bulk structure. When the laminate has this structure, in addition to the above effects, it is possible to prevent electrical conduction between the outermost layers in the stacking direction.
[0039] (25% compressive strength) If the 25% compressive strength of the laminate exceeds 800 kPa, the flexibility becomes insufficient and the conformability to the installed parts decreases. From the viewpoint of having sufficient flexibility and obtaining good conformability, the 25% compressive strength of the laminate is preferably 700 kPa or less, more preferably 600 kPa or less, even more preferably 500 kPa or less, even more preferably 400 kPa or less, and particularly preferably 350 kPa or less. If the 25% compressive strength of the laminate is less than 30 kPa, the mechanical strength will be insufficient. From the viewpoint of improving the mechanical strength, the 25% compressive strength of the laminate is preferably 60 kPa or more, more preferably 90 kPa or more, and even more preferably 120 kPa or more. The 25% compressive strength in the present invention can be measured according to the method described in the examples below.
[0040] (Electromagnetic wave shielding) If the electromagnetic shielding property of the laminate at a frequency of 100 MHz by the coaxial method is less than 10 dB, the blocking of electromagnetic noise is insufficient, and the influence of electromagnetic noise cannot be suppressed. The electromagnetic shielding property of the laminate at a frequency of 100 MHz by the coaxial method is preferably 11 dB or more, more preferably 12 dB or more, and even more preferably 13 dB or more. When the electromagnetic shielding property of the laminate at a frequency of 100 MHz by the coaxial method is equal to or more than the lower limit, electromagnetic noise can be blocked and the influence of electromagnetic noise can be suppressed. In the present invention, the electromagnetic wave shielding property can be measured by a coaxial method, and can be measured by the method described in the examples.
[0041] (Surface resistance value of conductive resin layer) The surface resistance of the conductive resin layer laminated on the laminate is 1.0×10 3 It is preferable that the resistance is 0.5×10 3 It is preferable that the resistance is Ω / sq or less, and 0.1×10 3 It is more preferable that the surface resistance value of the conductive resin layer is Ω / sq or less. By making the surface resistance value of the conductive resin layer 0.01 to 0.05, the conductivity of the conductive resin layer is increased, and the shielding property against electromagnetic noise can be improved. The lower the surface resistance value of the conductive resin layer, the higher the conductivity, so the lower limit is not particularly limited, but can be, for example, 0.1Ω / sq or more, and practically 1Ω / sq or more. In the present invention, the surface resistance value can be measured by a four-probe method in accordance with JIS K7194:1994, and can be measured by the method described in the Examples.
[0042] (Surface resistance value of insulating resin layer) The surface resistance of the insulating resin layer laminated on the laminate is 1.0×10 7 It is preferable that the resistance is Ω / sq or more, and 1.0×10 6It is more preferable that the surface resistivity exceeds Ω / sq. When the surface resistivity of the insulating resin layer is equal to or more than the above lower limit, it is possible to block electrical conduction in the stacking direction of the laminate. In the present invention, the surface resistance value can be measured by a four-probe method in accordance with JIS K7194:1994, and can be measured by the method described in the Examples.
[0043] (Asker C hardness) From the viewpoint of improving the flexibility and impact absorption of the laminate, the layer laminated on the outer layer side of the laminate preferably has an Asker C hardness of 50 or less. Moreover, from the viewpoint of improving the mechanical strength of the laminate, the layer laminated on the inner layer side of the laminate preferably has an Asker C hardness of 50 or more. In consideration of the above, the Asker C hardness of the conductive resin layer constituting the laminate is preferably 55 or more and 90 or less, and more preferably 60 or more and 80 or less. In consideration of the above, the Asker C hardness of the insulating resin layer constituting the laminate is preferably 45 or less, and more preferably 40 or less. The Asker C hardness of the conductive resin layer and the insulating resin layer can be adjusted by the density, thickness, etc. of each layer. The Asker C hardness of the conductive resin layer and the insulating resin layer in the present invention can be measured according to the method described in the examples below.
[0044] (density) The density of the laminate is 0.06 g / cm 3 More than 0.7g / cm 3 It is preferable that the concentration is 0.08 g / cm or less. 3 More than 0.6g / cm 3 More preferably, it is 0.10 g / cm or less. 3 More than 0.5g / cm 3 When the density of the laminate is within the above range, the flexibility is good and the ability to conform to the components on which the laminate is installed can be improved. The density of the laminate can be measured in accordance with JIS K7222:2005.
[0045] (Thickness) The thickness of the laminate is preferably 0.01 mm or more and 2.0 mm or less, more preferably 0.05 mm or more and 1.5 mm or less, and even more preferably 0.1 mm or more and 1.0 mm or less. When the thickness of the laminate is equal to or more than the lower limit, it is easy to ensure electromagnetic shielding properties, flexibility, and insulation properties. Also, when the thickness of the laminate is equal to or less than the upper limit, it is possible to respond to the trend toward thinner electronic devices.
[0046] (degree of crosslinking) In the conductive resin layer and the insulating resin layer constituting the laminate, the layer made of the foam is preferably crosslinked. The degree of crosslinking in all layers of the conductive resin layer and the insulating resin layer constituting the laminate is preferably 10% by mass or more and 70% by mass or less, more preferably 20% by mass or more and 60% by mass or less, and even more preferably 30% by mass or more and 50% by mass or less. When the degree of crosslinking of the laminate is equal to or more than the lower limit, sufficient crosslinking is formed, mechanical strength can be increased, and durability can be improved. In addition, when the degree of crosslinking of the laminate is equal to or less than the upper limit, flexibility is good, and conformability to the installed parts can be improved. The degree of crosslinking in the present invention can be measured according to the method described in the Examples below.
[0047] (Electrical conductivity in the lamination direction) It is preferable that the laminate has no electrical conductivity in the lamination direction. Here, electrical conductivity in the lamination direction of the laminate refers to the property of passing electricity between one outermost layer and the other outermost layer of the laminate. In other words, no electrical conductivity in the lamination direction of the laminate means that no electrical current flows in the lamination direction of the laminate. The lack of electrical conductivity in the lamination direction of the laminate ensures insulation in the lamination direction of the laminate, and prevents unexpected electrical current even if the laminate comes into contact with the circuit of an electronic device, thereby suppressing malfunction of the electronic device. The electrical conductivity in the lamination direction of the laminate of the present invention can be measured according to the method described in the examples below.
[0048] [Method of manufacturing laminate] The conductive resin layer of the laminate can be produced, for example, from a conductive resin composition containing an olefin-based resin, etc. The conductive resin layer can be produced as a foam by adding a foaming agent to the conductive resin composition as necessary and heating it to foam. The insulating resin layer of the laminate can be produced, for example, from an insulating resin composition containing an olefin-based resin, etc. The insulating resin layer can be produced as a foam by adding a foaming agent to the insulating resin composition as necessary and heating it to foam. Specifically, it is industrially advantageous to produce the compound by a method including the following steps (1) to (3). Step (1): A step of supplying each component of the conductive resin layer to a kneading device, melting and kneading the components to obtain a conductive resin composition. Step (2): A step of supplying each component of the insulating resin layer to a kneading device, melting and kneading the components to obtain an insulating resin composition. Step (3): The conductive resin composition and the insulating resin composition obtained in steps (1) and (2) are molded to a desired thickness and laminated to form a sheet-shaped laminate material.
[0049] In the above step (1), when the conductive resin composition contains a thermally decomposable foaming agent as the foaming agent, the composition is melted and kneaded at a temperature lower than the decomposition temperature of the thermally decomposable foaming agent. Examples of the kneading device in step (1) include extruders such as a single screw extruder or a twin screw extruder, a Banbury mixer, a roll, and other general-purpose kneading devices, with an extruder being preferred.
[0050] In the above step (1), when carbon black such as Ketjen black is blended, it may be difficult to ensure dispersibility in the conductive resin composition. Therefore, in order to improve dispersibility, it is preferable to use a conductive master batch in which the base resin is a polyolefin resin, preferably a polyethylene resin. From the viewpoint of improving dispersibility in the conductive resin composition, the content of carbon black in the conductive masterbatch is preferably 1.0 mass % or more and 30.0 mass % or less, more preferably 2.0 mass % or more and 25.0 mass % or less, and even more preferably 3.0 mass % or more and 20.0 mass % or less, relative to the total amount of the conductive masterbatch.
[0051] In the above step (2), when the insulating resin composition contains a thermally decomposable foaming agent as the foaming agent, the composition is melted and kneaded at a temperature lower than the decomposition temperature of the thermally decomposable foaming agent. Examples of the kneading device in step (2) include extruders such as a single screw extruder or a twin screw extruder, a Banbury mixer, a roll, and other general-purpose kneading devices, with an extruder being preferred.
[0052] In the above step (3), examples of the method for forming a laminate material by laminating the conductive resin composition and the insulating resin composition include a method in which layers made of the conductive resin composition and the insulating resin composition are separately prepared and laminated by pressure bonding or the like to form a laminate material, or a method in which the conductive resin composition and the insulating resin composition are co-extruded by an extruder or the like to form an integral material.
[0053] It is preferable to include a step of irradiating the laminate material obtained in step (3) with ionizing radiation to crosslink the laminate material after the above step (3). In the crosslinking step, the laminate material is irradiated with ionizing radiation so that the gel fraction of the crosslinked laminate material is 10% by mass or more and 50% by mass or less. Examples of the ionizing radiation used in the crosslinking step include α-rays, β-rays, γ-rays, and electron beams, and electron beams are preferred. The dose of ionizing radiation may be any dose that can obtain a desired degree of crosslinking, and is preferably 2 to 10 Mrad, more preferably 3 to 8 Mrad, and even more preferably 4 to 6 Mrad. The dose of ionizing radiation is influenced by the blending of the olefin resin and additives, and is usually adjusted while measuring the degree of crosslinking.
[0054] It is preferable to include a step of heating and foaming the laminate material obtained in step (3) to a temperature equal to or higher than the decomposition temperature of the foaming agent after the above step (3). In the foaming step, the temperature at which the laminate material is heated and foamed depends on the decomposition temperature of the thermally decomposable foaming agent used as the foaming agent, but is usually 140 to 300°C, preferably 150 to 260°C.
[0055] [How to use the laminate] The laminate of the present invention is used, for example, inside electronic devices. As electronic devices, preferred are mobile phones, tablet terminals, electronic paper, notebook PCs, video cameras, digital cameras, and other portable devices, vehicle-based electronic devices such as engine control units (ECUs) and advanced driver assistance systems (ADAS), and wearable terminal devices used in the form of watches and glasses. The laminate is disposed near electronic components that generate electromagnetic noise, and is used as an electromagnetic shield to suppress the electromagnetic noise. Thus, the laminate of the present invention can be suitably used as a sheet for components inside electronic devices that are sources of electromagnetic noise. The laminate is highly flexible, has conformability, and can be made thin, so that it can be appropriately disposed in a narrow space.
[0056] The laminate is also used as an impact absorbing material attached to or around a specific component inside an electronic device to prevent the component from being subjected to impact, and is also used as a sealing material to fill gaps inside the electronic device to prevent dust, moisture, etc. from entering the electronic device. That is, the laminate can be used as a shock absorbing material or a sealing material while being used as a conductive sheet.
[0057] [Adhesive tape] The laminate of the present invention may be used in an adhesive tape having the laminate as a substrate. The adhesive tape includes, for example, the laminate and an adhesive material provided on at least one surface of the laminate. The adhesive tape can be adhered to other members via the adhesive material. The adhesive tape may include an adhesive material provided on both surfaces of the laminate, or an adhesive material provided on one surface of the laminate.
[0058] The adhesive material may be one that at least includes an adhesive layer, and may be a single adhesive layer laminated on the surface of the laminate, or a double-sided adhesive sheet attached to the surface of the laminate, but is preferably a single adhesive layer. The double-sided adhesive sheet includes a substrate and adhesive layers provided on both sides of the substrate. The double-sided adhesive sheet is used to adhere one adhesive layer to the laminate and the other adhesive layer to another member. The adhesive constituting the adhesive layer is not particularly limited, and for example, an acrylic adhesive, a urethane adhesive, a rubber adhesive, etc. may be used. Furthermore, a release sheet such as release paper may be further attached onto the adhesive material. The thickness of the adhesive material is preferably from 5 to 200 μm, more preferably from 7 to 150 μm, and further preferably from 10 to 100 μm. EXAMPLES
[0059] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples in any way. The methods for measuring and evaluating the various physical properties in the present invention are as follows.
[0060] (degree of crosslinking) The degree of crosslinking of the laminates obtained in the Examples and Comparative Examples was measured as follows. A test piece of about 100 mg is taken so that each layer of the laminate is uniform, and the mass A (mg) of the test piece is precisely weighed. Next, this test piece is immersed in 30 cm of xylene at 120 °C. 3 After immersing the laminate in the solution for 24 hours, the insoluble matter on the wire mesh is collected by filtration through a 200-mesh wire mesh, vacuum-dried, and the mass B (mg) of the insoluble matter is precisely weighed. Next, the mass C (mg) of the carbon-based filler in the laminate is calculated from the weight of the laminate and the blending ratio of the carbon-based filler. The degree of crosslinking (mass%) is calculated from the obtained value using the following formula. Crosslinking degree (mass%) = 100 × ((BC) / A)
[0061] (density) The apparent density of the laminates obtained in the examples and comparative examples was measured in accordance with JIS K7222:2005.
[0062] (Thickness) The thickness of the foam sheets obtained in the examples and comparative examples was measured with a dial gauge.
[0063] (25% compressive strength) The 25% compression hardness of the laminates obtained in the examples and comparative examples was measured in accordance with JIS K6767:1999.
[0064] (Surface resistance value) The surface resistance of each of the single layers of the conductive resin layer and the insulating resin layer of the laminates obtained in the examples and comparative examples was measured by a four-probe method in accordance with JIS K7194:1994 using a product named "Loresta-GP MCP-T600" manufactured by Mitsubishi Chemical Corporation. The surface resistance of the conductive resin layer was measured at five randomly selected points on the surface of the conductive resin layer in the laminate, and the average value was taken as the surface resistance of the conductive resin layer. The surface resistance of the insulating resin layer was measured at five randomly selected points on the surface of the insulating resin layer in the laminate, and the average value was taken as the surface resistance of the insulating resin layer.
[0065] (Asker C hardness) The Asker C hardness of each of the single layers of the conductive resin layer and the insulating resin layer of the laminates obtained in the Examples and Comparative Examples was measured using an Asker Rubber Hardness Tester Type C (manufactured by Kobunshi Keiki Co., Ltd.) by contacting the indenter of the hardness tester with the surface layer of each layer. The measurement was performed at 25°C.
[0066] (Electromagnetic wave shielding) The electromagnetic shielding properties of the laminates obtained in the examples and comparative examples were measured by the coaxial method using the following measuring equipment at frequencies from 45 MHz to 3 GHz, and the electromagnetic shielding properties (dB) at 100 MHz were evaluated. ·Coaxial tube jig: Manufactured by Keycom Co., Ltd., product name “GPC-7” Network analyzer: Agilent Technologies, product name "E5071C-4K5"
[0067] (Electrical conductivity in the lamination direction) The electrical conductivity in the lamination direction of the laminates obtained in the Examples and Comparative Examples was evaluated as follows. Six commercially available 1.5V dry batteries were connected in series, and one copper wire extending from the miniature light bulb socket was connected to the positive terminal of the dry batteries connected in series. The other copper wire extending from the miniature light bulb socket was then attached to one of the outermost layers of the laminate to be measured. One end of a separately prepared copper wire was attached to the other outermost layer of the laminate to be measured, and the other end of the copper wire was connected to the negative terminal of the battery connected in series. If the LED miniature light bulb attached to the socket lit up at this time, it was evaluated as "power: yes", and if it did not light up, it was evaluated as "power: no".
[0068] [Example 1] (Preparation of Laminate) As a polyethylene-based resin, linear low-density polyethylene (LLDPE, manufactured by Japan Polyethylene Co., Ltd., product name "UJ960", MFR = 5g / 10min) was prepared. As a carbon-based filler, graphite (manufactured by Nippon Graphite Industries Co., Ltd., product name "F#3", average particle size 50μm, aspect ratio 0.075) was prepared. As a foaming agent, azodicarbonamide (manufactured by Otsuka Chemical Co., Ltd., product name "SO-G3"), which is a thermal decomposition type foaming agent, was prepared. As a decomposition temperature regulator, magnesium oxide was prepared. As an antioxidant, a phenol-based antioxidant (2,6-di-tert-butyl-p-cresol) and a sulfur-based antioxidant (dilauryl thiodipropionate) were prepared. Next, 100 parts by mass of the linear low-density polyethylene, 75 parts by mass of graphite, 8 parts by mass of azodicarbonamide, 1 part by mass of magnesium oxide, and 0.5 parts by mass of an antioxidant (phenol-based antioxidant:sulfur-based antioxidant=2:1) prepared above were melt-kneaded at 140° C. in a Plastomill to obtain a conductive resin composition (A1). Next, 100 parts by mass of the linear low-density polyethylene, 4 parts by mass of azodicarbonamide, 1 part by mass of magnesium oxide, and 0.5 parts by mass of an antioxidant (phenol-based antioxidant:sulfur-based antioxidant = 2:1) prepared above were melt-kneaded at 140°C in a Plastomill to obtain an insulating resin composition (B1). The obtained conductive resin composition (A1) and insulating resin composition (B1) were molded in a press machine in the lamination direction so that B1:A1:B1=1:1:1, into a long sheet having a thickness of 0.35 mm. Next, both sides of the long sheet-like laminate composition were irradiated with an electron beam to crosslink the laminate material so that the degree of crosslinking was adjusted to 40% by mass. Thereafter, this laminate material was continuously fed into a foaming furnace maintained at 250° C. by hot air and an infrared heater, where it was heated and foamed to obtain a laminate. The physical properties and evaluation results of this laminate are shown in Table 1.
[0069] [Example 2] A laminate was obtained in the same manner as in Example 1, except that the conductive resin composition (A2) was prepared by changing the amount of graphite in the conductive resin composition to 100 parts by mass and the amount of azodicarbonamide to 10 parts by mass in Example 1. The physical properties and evaluation results of this laminate are shown in Table 1.
[0070] [Example 3] As a polyethylene-based resin, a conductive master batch was prepared in which the base resin was low-density polyethylene and the carbon-based filler Ketjen black was contained (manufactured by Lion Specialty Chemicals Co., Ltd., product name "Leopound LDPE (M1150)", with a carbon black content of 3.0 to 25.0 mass%). In Example 1, the amount of linear low-density polyethylene in the conductive resin composition was changed to 50 parts by mass, and 50 parts by mass of the conductive master batch was added. Then, a laminate was obtained in the same manner as in Example 1, except that the amount of graphite was changed to 100 parts by mass, and the amount of azodicarbonamide was changed to 12 parts by mass to prepare a conductive resin composition (A3). The physical properties and evaluation results of this laminate are shown in Table 1.
[0071] [Example 4] A laminate was obtained in the same manner as in Example 3, except that the obtained conductive resin composition (A3) and insulating resin composition (B1) were molded in a press in the lamination direction so that B1:A3 = 1:1, and formed into a long sheet having a thickness of 0.25 mm.
[0072] [Example 5] A laminate was obtained in the same manner as in Example 1, except that the conductive resin composition (A4) was obtained by changing the azodicarbonamide content in the conductive resin composition to 0 part by mass. The physical properties and evaluation results of this laminate are shown in Table 1.
[0073] [Example 6] A laminate was obtained in the same manner as in Example 1, except that in Example 5, the conductive resin composition (A5) was used in which the amount of graphite in the conductive resin composition was changed to 100 parts by mass. The physical properties and evaluation results of this laminate are shown in Table 1.
[0074] [Example 7] As a polyethylene-based resin, a conductive master batch was prepared in which the base resin was low-density polyethylene and the carbon-based filler Ketjen black was contained (manufactured by Lion Specialty Chemicals Co., Ltd., product name "Leopound LDPE (M1150)", with a carbon black content of 3.0 to 10.0 mass%). In Example 5, the amount of linear low-density polyethylene in the conductive resin composition was changed to 50 parts by mass, and 50 parts by mass of the conductive master batch was added. Then, a laminate was obtained in the same manner as in Example 1, except that the amount of graphite was changed to 100 parts by mass, and the amount of azodicarbonamide was changed to 0 parts by mass to prepare a conductive resin composition (A6). The physical properties and evaluation results of this laminate are shown in Table 1.
[0075] [Example 8] In Example 7, the obtained conductive resin composition (A6) and insulating resin composition (B1) were molded in a press in the lamination direction so that B1:A6 = 1:1, and were formed into a long sheet having a thickness of 0.25 mm, and a laminate was obtained in the same manner as in Example 7.
[0076] [Example 9] A laminate was obtained in the same manner as in Example 7, except that the amount of azodicarbonamide in the insulating resin composition was changed to 6 parts by mass to form an insulating resin composition (B2).
[0077] [Comparative Example 1] A laminate was obtained in the same manner as in Example 1, except that only the obtained conductive resin composition (A1) was molded in a press into a long sheet having a thickness of 0.25 mm. The physical properties and evaluation results of this laminate are shown in Table 2.
[0078] [Comparative Example 2] A laminate was obtained in the same manner as in Example 1, except that a conductive resin composition (A7) was used in which the amount of graphite in the conductive resin composition was changed to 50 parts by mass. The physical properties and evaluation results of this laminate are shown in Table 2.
[0079] [Comparative Example 3] A laminate was obtained in the same manner as in Example 1, except that the conductive resin composition (A8) was prepared by changing the amount of graphite in the conductive resin composition to 25 parts by mass. The physical properties and evaluation results of this laminate are shown in Table 2.
[0080] [Table 1]
[0081] [Table 2]
[0082] In Examples 1 to 9, the laminates have a predetermined laminate structure and good results in 25% compressive strength and electromagnetic shielding properties, so that the laminates have excellent electromagnetic shielding properties, and good flexibility, so that they can easily be installed in electronic devices because they have excellent conformability to the parts to be installed. Furthermore, the laminates in Examples 1 to 9 block electricity in the stacking direction, so that even if the circuit of the electronic device is touched, unexpected electricity does not flow and the electronic device can be prevented from malfunctioning. In contrast, in Comparative Example 1, the result of 25% compressive strength was poor, and therefore flexibility was insufficient, and electricity flow in the stacking direction could not be blocked, and therefore it was unsuitable. Also, in Comparative Examples 2 and 3, the result of surface resistance was poor, and therefore the result of electromagnetic shielding property was also poor, and therefore it was unsuitable as a part that blocks electromagnetic noise. [Explanation of symbols]
[0083] 10...Conductive resin layer 20...Insulating resin layer
Claims
1. A conductive resin layer and an insulating resin layer containing a polyolefin resin laminated on at least one surface of the conductive resin layer, The 25% compressive strength is 30 kPa or more and 800 kPa or less, The electromagnetic shielding performance at a frequency of 100 MHz using the coaxial method is 10 dB or more. the conductive resin layer contains a polyolefin resin and a conductive filler, The surface resistance of the conductive resin layer is 1.0×10 3 Ω / sq or less, The surface resistance of the insulating resin layer is 1.0×10 7 Ω / sq or more, The insulating resin layer is provided on both sides of the conductive resin layer.
2. The laminate according to claim 1 , wherein the conductive filler is a carbon-based filler.
3. 3. The laminate according to claim 1, wherein the polyolefin-based resin comprises at least one selected from the group consisting of a polyethylene-based resin, a polypropylene-based resin, and an olefin-based elastomer.
4. Density: 0.06 g / cm 3 0.7g / cm or more 3 The laminate according to any one of claims 1 to 3, wherein:
5. The laminate according to any one of claims 1 to 4, having a thickness of 0.01 mm or more and 2.0 mm or less.
6. The laminate according to any one of claims 1 to 5, which has no electrical conductivity in the lamination direction.
7. 7. The laminate according to claim 1, wherein at least one of the conductive resin layer and the insulating resin layer is a layer made of a foam.
8. The laminate of claim 7 , wherein the layer of foam is crosslinked.
9. An adhesive tape comprising the laminate according to any one of claims 1 to 8 and an adhesive layer provided on at least one surface of the laminate.
Citation Information
Patent Citations
The electromagnetic wave shielding member
JP1985020195U
Electrically conductive resin composition
JP1988033443A
Amorphous metallic thin film laminar sheet for electromagnetic shielding
JP1994260790A
Electromagnetic shielding wave material and manufacturing method therefor
JP2003069284A
Foamed body for shielding electromagnetic wave
JP2004002567A